Meckel's diverticulum perforation by a wooden toothpick in a child: A case report - Abdulhafidh Kadhi; Stanley Crankson; Saud Al Jadaan (Elsevier, 2020)
Perforation of Meckel's diverticulum (MD) by ingested foreign body (FB) is an extremely uncommon cause of acute abdomen in children. We report on a 13-year-old boy who presented with right iliac fossa pain associated with anorexia, tenderness, guarding and rebound tenderness. Abdominal ultrasound showed findings of acute appendicitis. However, laparoscopy revealed a wooden toothpick perforating MD and a hyperemic appendix. The FB was removed and laparoscopic diverticulectomy and appendectomy performed. Perforation of MD by a FB is a diagnostic challenge and it should be included in the differential diagnosis of acute abdomen in children.